Declarativity and efficiency in providing services of general economic interest. Empirical study regarding the relation between heating costs and budget constraints - Dumitru Miron; Monica Aureliana Petcu; Iulia David Sobolevschi (Amfiteatru Economic)
Defined by each country separately, according to real options, circumstances and traditions, the services of general economic interest have an objective purpose in ensuring protection and security for population. The services of general economic interest involve both public and economic services and show characteristics of both fields, reflecting the capabilities of communities to organize, regulate and provide them. Considering the accessibility to the essential service of general economic interest of providing household heating, as an undeniable condition of consumer protection, an analysis has been made in this field, with reference to the concrete manner of providing these services. The goal of this endeavor was to emphasize the actual conditionalities induced by the budget constraints of households while ensuring the universality of the access to the essential heating service. The empirical study is based on a survey of 55 households in sector 2 of Bucharest that have access to gas heating systems, while they have different revenues and equipments. The processing of the gathered data allowed the procurement of certain indicators that explain how household revenues determine the access to the heating services and how the deficiencies of the insurance system of these services deepen the social polarization and increase the weightings of those living at the limit of subsistence.